A comparison of modelled serum cTnT and cTnI kinetics after 60 min swimming. (14th October 2022) - Cirer-Sastre, Rafel; Jiménez-Gaytán, Romario; Carranza-García, Luis Enrique; George, Keith; Apple, Fred S.; Navarro-Orocio, Ricardo; López-García, Ricardo; Reverter-Masía, Joaquín; Mayolas-Pi, Carmen; Morales-Corral, Pedro Gualberto; Legaz-Arrese, Alejandro
Abstract: Post-exercise elevations of cardiac troponin T (cTnT) and I (cTnI) are often used in isolation but interpreted interchangeably. Research suggests, however, that post-exercise cTn kinetic might differ with each isoform. In this cross-sectional observational study, we collected blood samples before, immediately after (5 minutes), and at 1-, 3-, 6-, 12-, and 24-hour post-exercise in a mixed cohort of 56 participants after a distance-trial of 60 min continuous swimming (age range from 14 to 22, 57.1% female). Cardiac troponin kinetics were modelled using Bayesian mixed-effects models to estimate time to peak (TTP) and peak concentration (PC) for each isoform, while controlling for participants sex, tanner stage and average relative heart rate during the test. Exercise induced an elevation of cTnT and cTnI in 93% and 75% of the participants, respectively. Cardiac troponin T peaked earlier, at 2.9 h (CI: 2.6 – 3.2 h) post-exercise, whereas cTnI peaked later, at 4.5 h (CI: 4.2 – 4.9 h). Peak concentrations for cTnT and cTnI were 2.5 ng/L, CI: 0 – 11.2 ng/L and 2.16 ng/L, CI: 0 – 22.7 ng/L, respectively. Additionally, we did not observe a systematic effect of sex and maturational status mediating cTn responses.